PROFILE OF ANTICANCER ACTIVITIES OF BROTOWALI (Tinospora crispa L.) PLANTS OFVARIOUS REGIONS IN EAST JAWA - Roihatul Mutiah; Laily Nurul Azizah; Rahmi Annisa; Anik Listyana (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2019)
Brotowali (Tinosporacrispa L) is a plant which has potential to be a chemopreventive agent. This study aims to determine the profile of anticancer activity of brotowali stem extracts (Tinosporacrispa L.), from several regions in East Java. The extraction was carried out by maceration method using 80% ethanol solvent. Then, anticancer activity test was carried out on MCF-7 breast cancer cell model using the Microtetrazolium (MTT) Assay method. The results of the anticancer activity test showed that 15 brotowali stem extracts taken from 5 locations in East Java had significant differences in anticancer activity (P 0.05). Brotowali extracts from Kanigoro, Blitar city, had the highest anticancer activity with an IC50 value of 30.64 g / mL.